2011
DOI: 10.1016/j.jcmg.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Modulates Vascular Inflammation in Atherosclerotic Rabbits

Abstract: Objectives We sought to determine the anti-atherosclerotic properties of pioglitazone using multi-modality non-invasive imaging techniques. Background Inflammation is an essential component of vulnerable or high risk atheromas. Pioglitazone, a peroxisome proliferator–activated receptor-gamma (PPAR-γ)agonist possesses potent anti-inflammatory properties. We aimed to non-invasively to quantify the anti-inflammatory effects of pioglitazone on atheroma using 18F-fluorodeoxyglucose (18F-FDG)-PET/CT and dynamic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Notably each group showed similar reductions in fasting plasma glucose and hemoglobin A1c levels. This study extends prior preclinical imaging evidence of decreased inflammation observed with pioglitazone (9,10) and may underlie the favorable clinical and ultrasound imaging results observed in the PROactive, CHICAGO, and PERISCOPE clinical trials.…”
Section: Atherosclerosissupporting
confidence: 77%
“…Notably each group showed similar reductions in fasting plasma glucose and hemoglobin A1c levels. This study extends prior preclinical imaging evidence of decreased inflammation observed with pioglitazone (9,10) and may underlie the favorable clinical and ultrasound imaging results observed in the PROactive, CHICAGO, and PERISCOPE clinical trials.…”
Section: Atherosclerosissupporting
confidence: 77%
“…Kinetic parameters v p (fraction of vascular space), K trans (wash-in constant from plasma to tissue compartment), v e (fraction of extra-vascular extracellular space), and K ep (wash-out constant from tissue to plasma compartment) were calculated using standard non-linear least squares fittings (22) in Matlab. The non-model based parameter area under the concentration curve (AUC) (6,1012) was also calculated at 1 (AUC1) and 2 minutes (AUC2) after injection of contrast agent (6) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Using this same acquisition K trans was found to decrease in the carotid arteries of patients treated with statins 8 . In a rabbit model of atherosclerosis, the non-modeling parameter AUC calculated from 2D turbo spin echo (TSE) DCE-MRI was found to significantly correlate with plaque microvessel density 911 . Furthermore, DCE-MRI was used in this same model to quantify therapeutic efficacy of several FDA approved (atorvastatin 10 , pioglitazone 11 ) and novel therapeutics (liposome encapsulated glucocorticoids, liver-X-receptor agonists 10 ).…”
Section: Non-invasive Quantitative Mr Imaging Of Endothelial Permeabmentioning
confidence: 99%
“…In a rabbit model of atherosclerosis, the non-modeling parameter AUC calculated from 2D turbo spin echo (TSE) DCE-MRI was found to significantly correlate with plaque microvessel density 911 . Furthermore, DCE-MRI was used in this same model to quantify therapeutic efficacy of several FDA approved (atorvastatin 10 , pioglitazone 11 ) and novel therapeutics (liposome encapsulated glucocorticoids, liver-X-receptor agonists 10 ). In the same model 12 K trans was demonstrated to increase during plaque progression, and to significantly correlate with plaque macrophages.…”
Section: Non-invasive Quantitative Mr Imaging Of Endothelial Permeabmentioning
confidence: 99%